Adsorption of Linear Alkylbenzene Sulfonate (LAS) on Eggshell Powder - I Made Wisnu Adhi Putra; I Gede Widhiantara (Natural B, Journal of Health and Environmental Sciences, 2015)
Linear Alkylbenzene Sulfonate (LAS) is the main constituent of the detergent active ingredients. Some negative effects may be appear if this compound enters the aquatic environment with high concentration. In this study, the adsorption of LAS on chicken eggshell powder was studied in different contact time, pH, and initial LAS concentration. The adsorption isotherm pattern was also investigated in two different models i.e. Langmuir and Freundlich. Eggshell powder was characterized using FTIR, XRD, and Surface Area Analyzer prior to adsorption test. The maximum amount of LAS adsorbed on eggshell powder was achieved at contact time of 45 minutes, pH of 7, and initial LAS concentration of 75 mg/L. LAS adsorption on eggshell powder was found to follow the Langmuir isotherm adsorption with the adsorption capacity (b) of 1.6218 mol/g, adsorption constant (K) of 6.1660 x 104 L/mol, and the adsorption energy (ΔG° ads) of 27.78 kJ/mol.